2016
DOI: 10.2967/jnumed.116.178483
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dosimetry for177Lu-PSMA I&T in Metastatic Castration-Resistant Prostate Cancer: Absorbed Dose in Normal Organs and Tumor Lesions

Abstract: Prostate-specific membrane antigen (PSMA)-targeted radioligand therapy is increasingly used in metastatic castration-resistant prostate cancer. We aimed to estimate the absorbed doses for normal organs and tumor lesions using 177 Lu-PSMA I&T (I&T is imaging and therapy) in patients undergoing up to 4 cycles of radioligand therapy. Results were compared with pretherapeutic Glu-NH-CO-NH-Lys-(Ahx)-[ 68 Ga(HBEDCC)] ( 68 Ga-PSMA-HBED-CC) PET. Methods: A total of 34 cycles in 18 patients were analyzed retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
158
4
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(179 citation statements)
references
References 30 publications
12
158
4
5
Order By: Relevance
“…Kratochwil et al [30] also found 50% decreased SUV max values but no attempt to correlate them with absorbed dose calculation was made. In line with our data, in a very recent study, Okamoto et al [33] also report only moderate correlation of pre-therapeutic SUVs with absorbed dose estimates using a PSMA inhibitor for imaging and therapy (PSMA I&T). Obviously, besides target expression, also other factors of tumour biology are present which determine therapy response.…”
Section: Comparison Of Absorbed Doses and Suv Max Valuessupporting
confidence: 79%
“…Kratochwil et al [30] also found 50% decreased SUV max values but no attempt to correlate them with absorbed dose calculation was made. In line with our data, in a very recent study, Okamoto et al [33] also report only moderate correlation of pre-therapeutic SUVs with absorbed dose estimates using a PSMA inhibitor for imaging and therapy (PSMA I&T). Obviously, besides target expression, also other factors of tumour biology are present which determine therapy response.…”
Section: Comparison Of Absorbed Doses and Suv Max Valuessupporting
confidence: 79%
“…Herrmann et al [39] found that the AD values for the SG are lower than those for the spleen. Physiological uptake in the LG and the SG has been observed in recent radionuclide therapy studies using 177 Lu-PSMA-I&T [41] and 177 Lu-DKFZ-PSMA-617 [42]. The kidneys and the LG were found to be the organs receiving the highest AD, respectively, in these studies.…”
Section: Discussionmentioning
confidence: 52%
“…The same applies to other radiosensitive organs and tissues such as gonads and red bone marrow. Note from Table 4 that the effective doses of [ 64 Cu]CuCl 2 are similar to those estimated for 177 Lu-PSMA, a typical agent used in TRNT [19]. However, the absorbed doses to normal organs are considerably higher for 177 Lu-PSMA than those of [ 64 Cu]CuCl 2 .…”
Section: Discussionmentioning
confidence: 52%